2022
DOI: 10.1002/jbt.22981
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin delays cell cycle progression into the G0/G1 phase via suspension of MAPK signaling pathway in intrahepatic cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (iCCA) derived from epithelial cells of bile ducts is highly aggressive tumor. Hesperidin extracted from citrus fruits is a promising antitumor compound. The purpose of this study is to explore molecular mechanism by which hesperidin affects cholangiocarcinoma progression. Cellular functional experiments were performed and subcutaneous transplant xenograft model was established. Our findings indicated that hesperidin suppressed iCCA cell proliferation in time‐ and concentration‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Similar to our findings, a previous study reported that hesperidin inhibits the PI3K pathway in chemically induced liver cancer tissues in rats [ 62 ]. Hesperidin also regulates the expression of genes involved in cell cycle progression to arrest the cell cycle by inhibiting the MAPK pathway in intrahepatic cholangiocarcinoma [ 63 ]. To the best of our knowledge, this study is the first to analyze the effects of hesperidin on the MAPK and PI3K signaling pathways in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, a previous study reported that hesperidin inhibits the PI3K pathway in chemically induced liver cancer tissues in rats [ 62 ]. Hesperidin also regulates the expression of genes involved in cell cycle progression to arrest the cell cycle by inhibiting the MAPK pathway in intrahepatic cholangiocarcinoma [ 63 ]. To the best of our knowledge, this study is the first to analyze the effects of hesperidin on the MAPK and PI3K signaling pathways in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary phytochemicals, such as hesperidin, are considered to contribute to cancer prevention (37,38). The safety of hesperidin and its anticancer activity have been previously demonstrated (41,65,66). The intervention of hesperidin in TS-induced abnormal pulmonary EMT and cell proliferation is through the p38 pathway, where phosphorylated p38 and phosphorylated c-Fos are attenuated by hesperidin.…”
Section: Discussionmentioning
confidence: 99%